Mid-career teachers' perceptions of self-guided professional growth: strengthening a sense of agency through collaboration. Issue 5 (19th October 2016) - Strahan, David
Abstract : Opportunities for self-guided professional development provided a context for exploring ways that mid-career teachers designed learning projects and articulated their perceptions of professional growth. In their applications for small grants for materials and released time, participants identified their own personal goals for improving instruction, designed plans of action, and assessed results. Intensive case studies with six participants documented ways that they integrated professional growth experiences to varying extents based on the nature of their relationships with colleagues. Those who benefited most from their participation had more collaborative relationships and used data more sophisticatedly. Although it is impossible to generalize beyond the context of this initiative, case studies like these affirm the importance of teacher voice and agency in professional development, especially when facilitated by opportunities for extensive conversations about learning and teaching.